Comparative Estimation of Nutritionally Important Chemical Constituents of Red Seaweed, Gracilariopsis longissima, Affected by Different Drying Methods - Md. Rahamat Ullah; Mousumi Akhter; Abu Bakker Siddique Khan; Farhana Yasmin; Md. Monjurul Hasan; Aovijite Bosu; Mohammed Ashraful Haque; Md. Mohidul Islam; Md. Amirul Islam; Yahia Mahmud (Journal of Food Quality)
In this study, the nutritional and phytochemical components of red seaweed, Gracilariopsis longissima, were assessed in relation to the effects of various drying methods (freeze, oven, and sun). Gracilariopsis longissima’s proximate composition differed significantly (P < 0.05) among the three drying techniques, with freeze-dried samples having significantly greater protein (30.63 ± 0.90% dry weight) and lipids (1.49 ± 0.05% dry weight) contents. Except for phosphorus and sulfur, the mineral concentrations were likewise considerably greater in the freeze-dried samples. The total amino acids (30.48 ± 0.06% dry weight) and fatty acids contents were substantially greater (P < 0.05) in the freeze-dried samples. In freeze-dried samples, the levels of essential amino acids (18.92 ± 0.02% dry weight) and unsaturated fatty acids (54.08 ± 0.07%) were substantially greater (P < 0.05). When compared to oven- and sun-dried samples, the total phenolic content (88.70 ± 2.19 mg GAE/g dry weight) and the flavonoid content (71.46 ± 2.17 mg QE/g dry weight) of freeze-dried samples was also substantially higher. Among the three distinct drying techniques used, the freeze-drying technique kept G. longissima’s higher nutritional and phytochemical components.